EFEKTIFITAS DOSIS ACTINOKOMPOS TERHADAP PENYAKIT LAYU FUSARIUM DAN PERTUMBUHAN TANAMAN TOMAT (Lycopersicum esculentum Mill.) (Effectiveness Dosages of ActinoCompost to Control Fusarium Wilt Disease and Growth Tomato (Lycopersicum esculentum Mill.)) - A.A.,, Djaya,; L.,, Supriati,; S. M.,, Noor, (AGRIPEAT, 2015)
ABSTRACTFusarium wilt of tomato caused by a soil borne pathogen Fusarium oxysporum f.sp lycopersici whichis an important disease in tomato plants in Indonesia and the world that led to the loss of tomatoproduction in many regions due to rapid wilting process that occurs in young and old plants and causea yield loss of up to 30%-50%. The purpose of research to determine the effectiveness of the dosagesof actinocompost against fusarium wilt disease and the response to the growth of tomato plants hasbeen carried out in the laboratory and screenhouse of Department of Agriculture, Faculty ofAgriculture, University of Palangkaraya, September to December 2012. The research design usedcompletely randomized design with six replications with five 5 level dose of actinokompos consists of:Ao (without compost or control), A1 (10 g compost polybag-1), A2 (20 g compost polybag-1), A3 (30 gpolybag compost-1), A4 (40 g compost polybag-1). Observations included: (1) disease intensity, (2) theeffectiveness of antagonist, (3) plant height and stem diameter of tomato at 3, 4, 5 weeks after planting(wap). Conclusions from this research show that (1). Applyed of actinocompost suppresing theintensity disease of fusarium wilt on tomato plants, increased plant height at 3-4 wap, increased thediameter of the plant stem at 3-5 wap, effectiveness of antagonist was execellent, (2). Applyingactinocompost at 10 g plant-1 is more efficient than other treatments because suppressed fusarium wiltintensity of 0% and the effectiveness of the antagonist has a very good value (> 69%).Keywords: Fusarium wilt, actinocompost, tomato, effectiveness antagonist